CIA Triad Validation in Intrusion Detection Using ACO Algorithm with RNN based Cognitive Mechanisms - Jayaganesh Jagannathan, M.Y. Mohamed Parvees (Mathematical Statistician and Engineering Applications, 2022)
Confidentiality is the process of verifying the one’s identity to allow them for the usage of registered application which is available in the remote place and serve the same to different end users. Integrity is the process of examining the supplied data is altered by someone or not. Availability ensuring the data supply to legitimate user. Intrusion detection is a key parameter to stop malicious action immediately at the same time it should be validated against CIA. Cognitive is the nascent technology which is strongly applying the concepts of it against discovery of malicious event. Bio Inspired algorithms are mainly applied to obtain optimized result in the process. Proposed solution for validating CIA along with intrusion detection named as ACO- RNN-C model to verify the CIA measurement. We have compared CIA validations against our previous findings and proved that ACO-RNN-C has given reasonable improvement in performance.